A Retrospective Descriptive Study of the Characteristics of Schizophrenia Patients - Laras Rima Dhani; Nurqoriah Susilawati (International Journal Labs, 2026)
Schizophrenia is a chronic mental disorder that significantly affects patients’ quality of life and contributes to a substantial global health burden. This research aimed to analyze the epidemiological profile and sociodemographic characteristics of schizophrenia patients at Bantarjaya Health Center, Bogor Regency, Indonesia. A retrospective descriptive design was employed using secondary data from the medical records of patients diagnosed with schizophrenia between January and June 2025. A total of 76 patients aged 16–75 years were included in the study. The variables analyzed consisted of age, gender, and marital status. The results showed that male patients slightly outnumbered female patients, with a ratio of 1.3:1 (56.5% vs. 43.5%). The highest prevalence was found in the young age group (16–30 years) at 38.1%, followed by the productive age group (31–45 years) at 36.8%. In terms of marital status, most female patients were married (60.6%), while the majority of male patients were unmarried (67.4%). The findings indicate a significant association between gender, age at onset, and marital status, where early onset in males may interfere with psychosocial development, including the ability to establish marital relationships. Conversely, later onset in females allows greater opportunities for marriage. In conclusion, schizophrenia predominantly affects individuals in their productive years, with notable differences in demographic characteristics between genders. These findings highlight the importance of early detection and tailored intervention strategies at the primary healthcare level to improve patient outcomes and social functioning.